Management of mullerian development anomalies: 9 years' experience of a tertiary care center - Lajya Devi Goyal; Balpreet Dhaliwal; Paramdeep Singh; Sandesh Ganjoo; Vikas Goyal (Wolters Kluwer Medknow Publications, 2020)
Objectives: This study aimed to analyze the clinical and imaging findings as well as the outcomes of patients with Mullerian duct anomalies. Materials and Methods: A retrospective analysis of 41 patients with Mullerian development anomalies treated in a tertiary care center in the past 9 years was done. The presenting symptoms, radiological findings, management, and the outcomes were evaluated. Results: According to the American Fertility Society's classification, 11 patients presented in Class I, 6 in Class II, and 24 in Class III of the classification. It was found that some of the defects such as the unicornuate uterus, a unicornuate uterus with noncommunicating rudimentary horn, and longitudinal vaginal septum were usually asymptomatic whereas disorders such as Mayer-Rokitansky-Küster-Hauser (MRKH), cervicovaginal atresia, and transverse vaginal septum presented with the absence of menarche, cyclical abdominal pain, and abdominal mass, respectively. Defects such as the bicornuate uterus, didelphys uterus, and septate uterus present with poor reproductive performance. Unicornuate uterus with communicating horn presented with rupture of the horn in the antenatal period, which was managed vigorously. Vaginoplasty with a skin graft and amnion graft had excellent results in MRKH syndrome. Patients with cervicovaginal atresia had a poor prognosis and ultimately required a hysterectomy. Hysteroscopic septal resection improved the reproductive performance in the patients with septate uterus. Conclusion: This study concluded that the management of uterine malformations is individualized depending on the symptoms and fertility concerns. Cervicovaginal atresia was associated with restenosis after surgery ultimately required a hysterectomy. MRKH had excellent results with McIndoe vaginoplasty. Optimal and timely management may lead to better outcomes.